TYLOCEPHALUM YESHWANROAE N. SP. (LECANICEPHALIDAE : BRAUN, 1900) FROM TRYGON SEPHEN AT RATNAGIRI, INDIA - PAWAR, R.G.; DANDWATE, R.R.; LONKAR, R.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The present communication deals with the new species yeshwantraoae from the genus Tylocephalum (Linton, 1890) is having scolex globular, some what rounded and divided into two regions, anterior is almost conical, posterior semicircular, neck, elongated, testes oval 20-30 in number, cirrus pouch in the middle of the segment, ovary "V" shaped, shell glands post ovarian. vitellaria follicular.